Analysis of determinants of renewable energy consumption in Indonesia - Wijayanti, Desi; Suparta, I Wayan; Marselina, Marselina (Penerbit Goodwood, 2025)
Purpose: This study aims to examine the determinants of renewable energy consumption in Indonesia, focusing on Gross Domestic Product (GDP), energy subsidies (SUB), urban population (POPs), and carbon dioxide (CO?) emissions over the period 1990–2023. Research methodology: A quantitative descriptive approach is applied using time series data from 1990 to 2023. The analysis combines the Error Correction Model (ECM) to capture short-term dynamics and long-term equilibrium, and Ordinary Least Squares (OLS) regression for estimating the relationships between variables. Results: In the short term, GDP and urban population exhibit a positive but insignificant effect on renewable energy consumption, while energy subsidies have a negative and significant effect. CO? emissions show a positive and significant effect. In the long term, GDP and CO? emissions maintain a positive and significant impact, energy subsidies remain negative and significant, and urban population continues to have a positive but insignificant influence. Simultaneous testing confirms that GDP, energy subsidies, urban population, and CO? emissions collectively influence renewable energy consumption in Indonesia. Conclusions: The findings highlight the importance of economic growth and environmental pressures in driving renewable energy use, while energy subsidies negatively impact its adoption. Limitations: The study is limited to four independent variables and does not account for technological innovation or policy changes beyond energy subsidies. Contribution: This research provides empirical evidence for policymakers to design strategies promoting renewable energy consumption, emphasizing economic growth, emission control, and subsidy reform.